A Case Study on Teaching and Learning Innovations Applied to Engineering Education - Soundattikar, S. A.; Naik, V. R. (Journal of Engineering Education Transformations, 2016)
Maintaining service quality in any service industry is a big challenge and engineering education is not an exception. The students possess different learning styles and accordingly teaching methods also vary. Some instructors deliver lecture, demonstrate or discuss. Some focus on applications while some emphasize on understanding. If there is a disparity between learning objectives and traditional teaching styles in engineering education, students become bored and inattentive in class. They may get unenthusiastic about the courses and the curriculum. Bloom’s taxonomy developed by Benjamin Bloom can be used in this context as this model can help teachers to teach a topic to the group of students with different levels of abilities, needs and learning styles. It supports the need to differentiate the curriculum so all the students are able to participate in the same content area during a lesson. The paper deals with the learning styles and few innovative teaching methods designed on the basis of Bloom’s Taxonomy, used for teaching Total Quality Management subject at Final year Mechanical class as a case study and the results obtained.